Pathophysiological Mechanisms in Non-Alcoholic Fatty Liver Disease: From Drivers to Targets - Alvaro Santos-Laso; María Gutiérrez-Larrañaga; Marta Alonso-Peña; Juan M. Medina; Paula Iruzubieta; María Teresa Arias-Loste; Marcos López-Hoyos; Javier Crespo (Biomedicines, 2021)
Non-alcoholic fatty liver disease (NAFLD) is characterized by the excessive and detrimental accumulation of liver fat as a result of high-caloric intake and/or cellular and molecular abnormalities. The prevalence of this pathological event is increasing worldwide, and is intimately associated with obesity and type 2 diabetes mellitus, among other comorbidities. To date, only therapeutic strategies based on lifestyle changes have exhibited a beneficial impact on patients with NAFLD, but unfortunately this approach is often difficult to implement, and shows poor long-term adherence. For this reason, great efforts are being made to elucidate and integrate the underlying pathological molecular mechanism, and to identify novel and promising druggable targets for therapy. In this regard, a large number of clinical trials testing different potential compounds have been performed, albeit with no conclusive results yet. Importantly, many other clinical trials are currently underway with results expected in the near future. Here, we summarize the key aspects of NAFLD pathogenesis and therapeutic targets in this frequent disorder, highlighting the most recent advances in the field and future research directions.